Soil, water and nitrogen management in common bean cultivation - Arf, Orivaldo; Rodrigues, Ricardo Antonio Ferreira; de Sá, Marco Eustáquio; Buzetti, Salatier; do Nascimento, Vagner (Pesquisa Agropecuaria Brasileira, 2004)
The appropriate cultural management enhance the plant efficiency on available resource utilization. This study aimed to evaluate the IAC Carioca Eté cultivar common bean performance as a function of soil management, sidedressing nitrogen rates and water level management. A randomized block design in a factorial scheme with four repetitions was used. The treatments were constituted by combination of three water levels, three soil management (moldboard plow + leveling disc harrow, heavy disc harrow + leveling disc harrow, and no tillage) and sidedressing nitrogen rates applied at 15 days after plant emergency (0, 30, 60, 90, and 120 kg ha-1). It was also used a sprinkle irrigation system and different cultural coefficients (Kc) for water management between plant emergency and harvest. The smallest water level showed grain yield similar to other levels but with the advantage of being cheaper. The soil tillage with moldboard plow allowed higher grain yield in relation to no till system and that was similar to the preparation with heavy disc harrow. The sidedressing nitrogen fertilization did not interfere in the grain yield.
Keywords: Phaseolus vulgaris; moldboard ploughs; disc harrows; sprinkler irrigation; nitrogen fertilizers